Smart Finder Using IoT System - Muhammad Zafri Hakim Bin Abdul Nasir; Raja Muhammad Hazim Bin Raja Noradzmi (Universitas Negeri Padang, 2022)
Practical learning in Electronics requires handling and managing many electronic components, tools, and equipment. A study has been done to improve the time-consuming process to locate these parts in an electronic workshop. As a result, Smart Finder was designed to replace the manual search method. This product utilizes the Internet of Things (IoT) as a link between a smartphone and NodeMCU microcontroller. Connectivity between the phone and microcontroller enables users to locate electronic parts from anywhere within the communication coverage. Smart Finder Application on the smartphone is built with MIT App Inventor. After the required login process , users need to select the component/part on the menu in the application. Once the component/part is selected, LED which acts as indicator on the selected component/part storage turns on. These few steps would simplify and expediate the searching process. Based on the result of the questionnaires, more than 95% of respondents agreed that Smart Finder helps in saving time in preparing parts for practical classes. Further improvements on the project would be adding better security measures, application for IOS users, and more useful interfaces or features to improve workshop management in Electronic Program.